Evaluation of Long-Term Respiratory Effects of Exposure to Welding Fumes - Meshack Achore; Mahsa Taghiakbari; Alfi A. Parfi; Catherine Lemiere; Mariam El-Zein; Mounia Rhazi; Denyse Gautrin; Eva Suarthana (Fakultas Kedokteran Universitas Kristen Indonesia, 2019)
Abstract Welding fumes are known to cause respiratory health problems. We aimed to evaluate the long-term respiratory effects of exposure to welding fumes. Inception cohorts of welding, plumbing, and heating apprentices were prospectively contacted 7-17 years post-apprenticeship. Questionnaires, as well as spirometry and non-specific bronchial hyperresponsiveness (NSBHR) tests were repeatedly administered. A long-term evaluation was done in 71 former apprentices at the Hôpital du Sacré-Cœur de Montréal between 2013 and 2017. Post-apprenticeship exposure to welding fumes and gasses was evaluated using three methods: self-report, expert assessment and the asthmaspecific job exposure matrix. The incidence of wheezing and excessive lung function decline, given continued post-apprenticeship exposure to welding fumes, was estimated using Cox regression. Incident wheezing was found in 18.8% of subjects, and excessive lung function decline was observed in 12.7% of subjects. All three exposure assessment methods consistently showed that subjects with continued, post-apprenticeship exposure to welding fumes or gasses had a lower risk of developing wheezing symptoms or excessive decline in lung function, although none of the associations were significant. In conclusion, continued post-apprenticeship exposure to welding fumes does not seem to increase the risk of developing long-term respiratory outcomes.Keywords: apprentices, lung function, occupational, welding Abstrak Asap dan gas pengelasan (welding fumes and gasses) diketahui dapat menyebabkan masalah pernapasan. Penelitian ini dilakukan untuk mengevaluasi efek pernapasan jangka panjang dari pajanan asap dan gas pengelasan. Mantan peserta sekolah kejuruan pengelasan secara prospektif dihubungi 7-17 tahun pasca-pendidikan. Subjek penelitian melengkapi kuesioner, uji spirometri dan uji bronkus non-spesifik. Evaluasi jangka panjang dilakukan pada 71 subjek di Hôpital du Sacré-Cœur de Montréal antara tahun 2013 dan 2017. Pajanan asap dan gas pengelasan pascapendidikan dievaluasi menggunakan tiga metode: laporan oleh pekerja, penilaian oleh ahli dan penggunaan matriks pajanan di tempat kerja pekerjaan khusus. Hubungan antara pajanan asap dan gas pengelasan dengan insidens mengi dan penurunan fungsi paru-paru berlebihan dievaluasi menggunakan regresi Cox. Insidens mengi ditemukan pada 18,8% subjek, dan penurunan fungsi paru berlebihan diamati pada 12,7% subjek. Ketiga metode penilaian pajanan secara konsisten menunjukkan bahwa subjek dengan pajanan asap dan gas pengelasan pasca-pendidikan memiliki risiko lebih rendah terkena gejala mengi atau penurunan fungsi paru-paru yang berlebihan, meskipun tidak ada hubungan yang bermakna. Sebagai kesimpulan, pajanan asap dan gas pengelasan jangka panjang tampaknya tidak meningkatkan risiko penurunan fungsi pernapasan.Kata kunci: fungsi paru, pekerjaan, asap dan gas pengelasan